The Role of Digital Technology in Optimizing Education at Pesantren Muhammadiyah Boarding School Yogyakarta - Al-hakim, Hamka; Dartim, Dartim; Chehdimae, Hamdan (Universitas Muhammadiyah Surakarta, 2024)
This study aims to find out how the application and utilization of digital technology in the pesantren Muhammadiyah Boarding School Yogyakarta located in Bokoharjo, Sleman, DIY. The study used qualitative methods with a phenomenological approach. Data collection was conducted by interviewing the head of the Islamic boarding school caregiver as well as educators at Muhammadiyah Boarding School Yogyakarta. Data analysis is presented descriptively. The results showed that the Muhammadiyah Boarding School yogyakrta has completed the digitization of learning in keeping up with the times in order to remain dynamic, and continue to exist. SBM Islamic boarding schools have strong policies and commitments in efforts to develop and utilize digitalization., Islamic boarding school caregivers believe that although pesantren are synonymous with religious nuances and the Quran, human resources in it must be aware and literate of technological developments. This effort is supported by adequate facilities in the classroom, each of which has a projector as one of the learning media. This study concluded that although the implementation of digital technology has not been fully implemented at Muhammadiyah Boarding School Yogyakarta, several parties have felt the benefits, including caregivers, educators and guardians, which are more practical and time-saving. The pesantren also continues to strive so that the digitization system can help on all fronts, on the other hand, the pesantren in planning and implementation must be carefully prepared so that everything runs optimally.